Sistemas de Alimentação com Livre Escolha e Semi Livre Escolha para Poedeiras - Sakomura, N. K.; daSilva, R.; Moreno, S. Q.; Malheiros, E. B.; Araujo, W. A.; Seixas, JRC (Revista Sociedade Brasileira Zootecnia, 1997)
This research was carried out to verify the ability of laying hens to select food in order to meet their requirements for protein and energy. Ninety-six Hy-Line White laying hens, 45 weeks old, were allotted to a randomized block design with two blocks (two ranges of body weight), four treatments, and three replicates of four hens in each block. The treatments consisted of four different feeding systems: I-Conventional feeding represented by a complete ration composed of 60% ground corn and 40% protein concentrate; 2-Free-choice feeding with ground corn, protein concentrate and oyster shells fed in feeders with three separate compartments; 3-Semi free-choice feeding with whole corn grain, protein concentrate and oyster shells in the same proportion in one feeder; 4-Free-choice feeding with whole corn grain, protein concentrate and oyster shells fed in feeders with three separate compartments. The results indicated that the hens, in spite of age, adapt to different feeding systems, and that they can select feed to meet their nutrient requirements. The semi free-choice and free-choice feeding systems with whole corn grain resulted in the same performance compared to conventional feeding, but shell quality was not improved by oyster shell supplementation. However, the worst performance was with free-choice feeding with ground corn, which indicated that in the free-choice feeding system the use of whole corn grain is recommended.
Free-choice and semi free-choice feeding systems for laying hens
Keywords: free-choice; whole grain corn; laying hens; Nutrition; Feeding system; semi free-choice